Model Peramalan Harga Telur Ayam Ras di Pasar Tradisional dan Modern Kota Jambi - Yessy Dwinata S; Bagus Pramusintho; Firmansyah Firmansyah; Fachroerrozi Hoesni (Universitas Batanghari Jambi, 2022)
This study aims to find out the volatility of the price of chicken eggs and compile a proper forecasting model for the price of chicken eggs in the Traditional and Modern market of Jambi City. The object of the study is the price of chicken eggs in the Traditional and Modern markets of Jambi City using quantitative descriptive methods using skunder data. For the type of data used in this study is time series data in the form of weekly data on the price of chicken eggs for the period 2018 to September 2021 sourced from the National Strategic Food Price Information Center. Data analysis is carried out through an econometric approach in answering its objectives, using model analysis (ARIMA), ARCH / GARCH model. Based on the results of data processing, the ARIMA model is the best model for forecasting the price of chicken eggs in the traditional jambi market. While the ARCH model is the best model for forecasting the price of chicken eggs in the Modern market of Jambi City. The results of high price forecasting are found in the Traditional Market of Jambi City with an average of Rp. 21,543.35,-per kg from October to December 2021. From the results, there is volatility in the Traditional and Modern markets of Jambi City which is seen based on CSD (conditional standard deviation), and high volatility and often occurs in the Traditional Jambi City market with a volatility value of 0.01009950. The policy of pricing the sale of chicken eggs that is set nationally every year must be reviewed again with regard to fluctuations in the price of chicken eggs at the consumer level that can increase beyond the price set by the government, and the government's policy for stabilization of the price of chicken eggs in the market both downstream needs to be followed by policies on upstream subsystems, for example, the production input price policy is specific to chicken farmers, especially the price of animal feed raw materials (especially corn). As well as the existence of market operations in Jambi's production should be able to be done and studied its sustainability in order to be one of the solutions to maintain the stabilization of chicken egg prices.